2016
DOI: 10.21511/bbs.11(2).2016.07
|View full text |Cite
|
Sign up to set email alerts
|

The changing market efficiency of the Nairobi securities exchange

Abstract: This paper tests for market efficiency changes of the Nairobi Securities Exchange (NSE) after the year 2000 and determines whether technological advancements have led to an increase in the market efficiency. The data that are used are the NSE 20 share index over the period, January 2001 to January 2015 and the NSE All Share Index (ASI) from its initiation, in February 2008 to January 2015. The data analysis method applied is the variance ratio test. The study finds that the market efficiency of the NSE has inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, Abou-Moghli, Al Abdallah and Al Muala (2017) found that innovation has a direct positive impact on competitive advantage through its dimensions (time, quality, cost, and flexibility) and that banks should support innovation in all aspects of business and operations. Njuguna (2016) empirically revealed that collaborative networks, innovation, product diversification and business development services have a positive significant relationship with the competitive advantage of SMEs youth enterprises. Furthermore, examined the link between SMEs performance and competitive advantage in Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Similarly, Abou-Moghli, Al Abdallah and Al Muala (2017) found that innovation has a direct positive impact on competitive advantage through its dimensions (time, quality, cost, and flexibility) and that banks should support innovation in all aspects of business and operations. Njuguna (2016) empirically revealed that collaborative networks, innovation, product diversification and business development services have a positive significant relationship with the competitive advantage of SMEs youth enterprises. Furthermore, examined the link between SMEs performance and competitive advantage in Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 99%